On the uniform convergence of Fourier Series - Rakhimov, Abdumalik (Institute for Mathematical Research (INSPEM), Universiti Putra Malaysia, 2016)
We prove theorems on the uniform summabilty of Fourier-Laplace series of distributions from the Sobolev spaces with negative smoothness defined on a unique sphere.